Balancing Self-Love: A Dichotomy of Amour Propre and Amour De Soi in Button Button by Richard Matheson: - Anwar, Muhammad Javaid; Saeed, Fazila (Educalitra: English Education, Linguistics, and Literature Journal, 2024)
Amour Propre, which is frequently interpreted as self-love or self-esteem is reflected in the intentions and deeds of the characters in literary works. This study examines Richard Matheson's short story Button, Button through the lens of Jean-Jacques Rousseau's concepts of Amour De Soi and Amour-Propre. The purpose of the study is to analyze how the characters of Norma and Arthur embody these concepts with Arthur representing Amour De Soi and Norma exemplifying corrupted Amour-Propre. Utilizing a qualitative analysis approach, the study explores the characters' actions and motivations within the narrative to uncover the implications of their respective forms of self-love. The findings reveal the dangers of allowing Amour- Propre to become excessive or corruptible as seen through Norma's relentless pursuit of material desires leading to tragic consequences. Furthermore, the study underscores the importance of maintaining a balance between self-love and consideration for others highlighting the virtues of a more balanced and self-respecting approach to life as demonstrated by Arthur's contrasting fate.